Molecular diffusion under confinement - Kärger, Jörg (Diffusion Fundamentals, 2005)
With reference to molecular transport in manifold media of porous structure, a survey is given on the ample spectrum of diffusion phenomena under confinement. The presentation is mainly based on the evidence provided by pulsed field gradient NMR and by interference and IR microscopy. These "microscopic" techniques of diffusion measurement are particularly powerful for exploring the diverse features of molecular propagation in complex systems. The presented data cover the peculiarities of molecular diffusion under the regime of "intracrystalline" zeolitic diffusion, refer to deviations from normal diffusion and deal with the practically particularly important case where the overall diffusion process includes molecular propagation in the gas phase. In many cases, the reported experimental studies have been performed in immediate response to theoretical issues including single-file diffusion and sorption hysteresis. Simultaneously, they have given rise to new challenges for basic research correlating equilibrium and non-equilibrium phenomena of molecular propagation.